1995
DOI: 10.1177/001979399504800410
|View full text |Cite
|
Sign up to set email alerts
|

International Trade and Worker Displacement: Evaluation of the Trade Adjustment Assistance Program

Abstract: The Trade Adjustment Assistance (TAA) program offers unemployment compensation and re-employment adjustment services to workers who lose their jobs due to increased import competition. In 1981 and again in 1988, the program rules were changed to shift the emphasis from compensation to training. This paper examines the pre-layoff characteristics and post-layoff labor market experience of two nationally representative samples of TAA program participants, one of which participated in the program just before the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 4 publications
1
20
0
2
Order By: Relevance
“…More recently, Decker and Corson (1995) used a survey of TAA participants between 1988 and 1989 to evaluate the impact of the 1988 amendments to the program that mandated participation in a training program. The authors find that the 1988 changes in the TAA program increased participation in training programs, reduced the amount of TRA collected by beneficiaries, and led to a decline in the duration of unemployment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently, Decker and Corson (1995) used a survey of TAA participants between 1988 and 1989 to evaluate the impact of the 1988 amendments to the program that mandated participation in a training program. The authors find that the 1988 changes in the TAA program increased participation in training programs, reduced the amount of TRA collected by beneficiaries, and led to a decline in the duration of unemployment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two previous ITG studies found no positive impacts of ITG participation on wages (Benus et al, 1996;Whittaker, 2002). Studies of other programs also found no impact on wages (Corson and Haimson, 1996;Decker and Corson, 1995). However, some quasi-experimental studies have found positive impacts on wages (Benus and Byrnes, 1993;Jacobson et al, 1994;Hollenbeck and Huang, 2003).…”
Section: Overall Impactmentioning
confidence: 99%
“…Prior research into the effectiveness of public-funded training has frequently concluded that for the majority of workers, such programs are ineffective (Decker and Corson 1995;Leigh 1991;LaLonde 1995). However, Jacobson, LaLonde, and White / Displacement-Related Earnings Losses 227 Table 2 Sullivan (1994) reported long-run benefits for workers completing relatively rigorous community college-level vocational and academic courses.…”
Section: Evaluation Of Taa and Ataamentioning
confidence: 99%